2018
DOI: 10.1186/s12875-018-0875-6
|View full text |Cite
|
Sign up to set email alerts
|

Patient factors that affect trust in physicians: a cross-sectional study

Abstract: BackgroundWhile trust in physicians has been rigorously investigated regarding its concept, measurement, and factors, the studies have mainly focused on the attributes of the physicians. This approach can lead to a limited understanding of trust in physicians as trust is based on the relationship, an interaction of both parties: patients and physicians. This study aimed to investigate the factors for trust in physicians among the Koreans by focusing on patients’ traits which are related to their subjective per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 28 publications
(34 reference statements)
3
36
0
2
Order By: Relevance
“…In Italy the general population has a wide-ranging understanding of skin diseases and the central role of dermatologists in skin care. Patients are looking for technical competence and loyalty, because these lead to a more trusted and satisfactory physician-patient relationship [10][11][12][13]. Similarly in our study in Poland, opinions about doctors have the greatest value and importance for patients.…”
Section: Dermatologist's Image According To Non-medical Studentssupporting
confidence: 53%
“…In Italy the general population has a wide-ranging understanding of skin diseases and the central role of dermatologists in skin care. Patients are looking for technical competence and loyalty, because these lead to a more trusted and satisfactory physician-patient relationship [10][11][12][13]. Similarly in our study in Poland, opinions about doctors have the greatest value and importance for patients.…”
Section: Dermatologist's Image According To Non-medical Studentssupporting
confidence: 53%
“…Journal of Multidisciplinary Healthcare 2021:14 conflicts with the findings of Kim et al 24 and Croker et al 25 These studies found that the relationship between the level of patient trust and SAHS is positive; that is, the higher the reported SAHS rating, the greater the likelihood of a higher level of trust. Croker et al 25 conducted their study based on a larger sample size, which explains the difference in findings compared to our study.…”
Section: Dovepressmentioning
confidence: 89%
“…The lack of association between some of these factors and level of patient trust has been found in many different previous studies. 24 , 26 …”
Section: Discussionmentioning
confidence: 99%
“…Second, unhealthy lifestyles, like smoking, drinking, and physical inactivity are linked with poor health conditions. People in poor health conditions are more likely to have negative experiences in the healthcare system and be less satis ed with it [18]. Lower patient satisfaction tends to have decreased the probability of seeking healthcare [19].…”
Section: Discussionmentioning
confidence: 99%